Cortactin is associated with perineural invasion in the deep invasive front area of laryngeal carcinomas - Ambrosio, Eliane Papa [UNESP]; Rosa, Fabiola Encinas [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; Rios Villacis, Rolando Andre; Coudry, Renata de Almeida; Tagliarini, José Vicente [UNESP]; Soares, Fernando Augusto; Kowalski, Luiz Paulo; Rogatto, Silvia Regina [UNESP] (W B Saunders Co-elsevier Inc, 2011)
The cortactin gene, mapped at 11q13, has been associated with an aggressive clinical course in many cancers because of its function of invasiveness. This study evaluated CTTN protein and its prognostic value in the deep invasive front and superficial areas of laryngeal squamous cell carcinomas. The transcript expression levels were evaluated in a subset of cases. Overexpression of CTTN cytoplasmatic protein (80% of cases in both the deep invasive front and superficial areas) and transcript (30% of samples) was detected in a significant number of cases. In more than 20% of cases, observation verified membrane immunostaining in the deep invasive front and superficial areas. Perineural invasion was significantly associated with N stage and recurrence (P = .0058 and P = .0037, respectively). Higher protein expression levels were correlated with perineural invasion (P = .004) in deep invasive front cells, suggesting that this area should be considered a prognostic tool in laryngeal carcinomas. Although most cases had moderate to strong CTTN expression on the tumor surface, 2 sets of cases revealed a differential expression pattern in the deep invasive front. A group of cases with absent to weak expression of CTTN in the deep invasive front showed good prognosis parameters, and a second group with moderate to strong expression of CTTN were associated with an unfavorable prognosis, suggesting an association with worse outcome. Taken together, these results suggest that the deep invasive front might be considered a grading system in laryngeal carcinomas and that cortactin is a putative marker of worse outcome in the deep invasive front of laryngeal carcinomas. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Deep invasive front; Laryngeal squamous cell carcinomas; Cortactin; TMA; qRT-PCR